STUDIES ON THE IDENTIFICATION OF CONSTITUENTS IN ETHANOL EXTRACT OF RADIX GLYCYRRHIZAE AND THEIR ANTICANCER ACTIVITY - Shi, Xiaoli; Zou, Ming; He, Jing; Xie, Hai; Li, Xu (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The main functions of Radix Glycyrrhizae include regulating middle warmer, moistening lung, relieving toxicity, harmonizing property of drugs which is a traditional Chinese medicine widely used in clinical settings. The objective of the paper is to isolate and identify the constituents in ethanol extract of Radix Glycyrrhizae, and to study their anticancer activity. Materials and Methods: Column chromatography, ODS column chromatography, preparative thin layer chromatography and NMR spectroscopy techniques were used to isolate compounds from ethanol extract of Radix Glycyrrhizae; optical microscopy and flow cytometry were used to determine the anticancer effect of Radix Glycyrrhizae extract. Results: Four compounds were isolated from the ethanol extract of Radix Glycyrrhizae, namely oleanolic acid, isoliquiritin, glycyrrhetinic acid and licochalcone A. Optical microscopic observation showed that the growth of gastric cancer cell line SGC-7901 was inhibited in the experimental groups, and apoptotic morphological changes were observed in adherent cells; flow cytometry with PI staining showed that Radix Glycyrrhizae extract could induce SGC-7901 cell apoptosis within a concentration range of 0.5-1.5 mg/mL, compared with the control group, the apoptosis was positively correlated with the drug concentration, which exhibited an apparent dose-dependence. Conclusion: We conclude Ethanol extract of Radix Glycyrrhizae has an anti-proliferative activity on SGC-7901 cells.